An Analysis Of Sense Based Sentences In One Half Love Comic - Kristiani, Relis, Dra. Siti Zuhriah, M. Hum, Agus Wijayanto, Drs., M. A., Ph. D. (2013)
This research deals with sense based sentences in One Half Love Comic. The aims of this research are to describe the type of sense based sentences and to describe the illocutionary act of sense based sentences found in One Half Love Comic. The type of this research is descriptive qualitative research. The researcher uses One Half Love Comic as the data source. The data of this research are simple declarative sentences. The researcher employs documentation as the method of collecting data with the techniques: reading, underlying, identifying and classifying the data. In analyzing the data, the writer describe the type of sense based sentences found in One Half Love Comic by referring to the theory of sense properties of sentences by Hurford and Heasley (1983) and describing illocutionary act of sense based sentences by Peccei (1999). The result of this research shows that there are three types of sense based sentences from the thirty seven data (100%) found in one half comic. They are analytic sentence (1 datum/ 2, 70%), synthetic sentence (31 data/ 83, 79%), and contradiction sentence (5 data/ 13, 51%). The illocutionary act is Amazing, Requesting, Confusing, Warning, Informing, Supporting, Surprising, Worrying, Promising, Persuading, want, Shocking, Knowing, Annoying, Regretting, Lying, Convincing, Up to, Asking, Suggesting, Proud and commanding.